SUSTAINABLE CONFERENCE TOURISM AS A PREREQUISITE FOR THE FUTURE DEVELOPMENT OF BUSINESS TOURISM: THE CASE OF HOTEL NORCEV - Botić, Aleksandra; Vujko, Aleksandra; Panić, Aleksa (The Business of Tourism, 2024)
This paper examines the role of sustainable conference tourism as a key prerequisite for the future development of business tourism, focusing on Hotel Norcev on Fruška Gora. The paper analyzes sustainable development and its impact on the competitiveness and success of business tourism in the future. The subject of the study is to explore the role of sustainable conference tourism as a crucial factor for the future development of business tourism. Paper started from the initial hypothesis that sustainability is a key factor for the development of business tourism. The tasks of the study included investigating and analyzing sustainable conference tourism, analyzing factors significant for business tourism, conducting research among hotel guests, analyzing the collected results, and developing recommendations for sustainable operations. The results showed that the application of sustainable principles significantly enhances the hotel’s competitiveness and suggests the implementation of ecological practices in all segments of business tourism.